Prediction of the performance of elite male trampolines based on body composition - Ercis, S. (Journal of Education and Training Studies, 2018)
Main purpose of this study was Prediction of the performance of elite male trampolines based on body composition indices. To this aim, 45 male athletes (age 14.17±2.86 yrs, athletic experience 7.22±3.64 yrs and competitive experience 3.31±2.44 yrs), who participated in the national trampoline team's preparation camps for participation at the 2014 Asian Games in four age categories included Children (ages 11 and 12 yrs), Juniors (ages 13 and 14 yrs), Adolescents (ages 15 to 17 yrs) and Seniors (ages 18 yrs <) were selected using targeted sampling. Variables of study included 24 body composition indices which were measured using standard procedures and instruments. Data were analyzed using Pearson correlation coefficient and multiple regression models at the 0.05 significance level. Results of study showed that, among all relationships between variables, only the relationships of the shoulder belt muscle strength (r=0.294) with performance are statistically significant and in other cases, observed relationships were not statistically significant (p>0.05). Findings of this study suggest that, in the high competitive level of trampoline body composition indices have not predictive role in preparation programs of elite male trampolines.